NATIONAL TRANSFORMATION OF THE POPULATION OF THE UZBEK SSR DURING THE WAR - Kamola Davlyatalievna Saipova, (EPRA International Journal of Research and Development (IJRD), 2022)
Resettlement peoples as a means of solving the problems of national minorities is characteristic of totalitarian states. In during World War II, it became apparent that the idea of mass migrations found its supporters among democratically oriented politicians in many countries. Undoubtedly, this was facilitated by disappointment in the system of protecting the rights of national minorities, which collapsed at the end of the 30s of the twentieth century, as well as the very fact of the actualization of conflicts between centuries of neighboring peoples. The author, on the basis of a broad study, revealed the dynamics of the national composition of the population of the Uzbek SSR during the Second World War.